2011
DOI: 10.1007/s12562-011-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Selection response and realized heritability for growth in three stocks of the Pacific oyster Crassostrea gigas

Abstract: To estimate response to selection and realized heritability for shell height, a one-generation selection was performed in the Pacific oyster Crassostrea gigas using three stocks from China (stock C), Japan (stock J), and Korea (stock K). Applying about the same intensity of selection in the upward direction, three selected and three control lines were created, which were reared under the same environmental conditions at larvae, spat, and grow-out stages. Stock C and stock J showed significantly higher response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 21 publications
3
64
0
Order By: Relevance
“…Recently, Li et al . () reported realized heritability estimates for shell height resulting from mass selection ranged from 0.149 to 0.402 in C. gigas at 12 months of age. In other oyster species, heritability for shell height was 0.34 in the Chilean oyster Ostrea chilensis (Toro & Newkirk ); and was 0.11 at 6 months and 0.19 at 18 months in the European oyster Ostrea edulis (Toro & Newkirk ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Li et al . () reported realized heritability estimates for shell height resulting from mass selection ranged from 0.149 to 0.402 in C. gigas at 12 months of age. In other oyster species, heritability for shell height was 0.34 in the Chilean oyster Ostrea chilensis (Toro & Newkirk ); and was 0.11 at 6 months and 0.19 at 18 months in the European oyster Ostrea edulis (Toro & Newkirk ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, heritability was the highest for shell height (0.49 AE 0.25). Recently, Li et al (2011) reported realized heritability estimates for shell height resulting from mass selection ranged from 0.149 to 0.402 in C. gigas at 12 months of age. In other oyster species, (Toro & Newkirk 1991); and was 0.11 at 6 months and 0.19 at 18 months in the European oyster Ostrea edulis (Toro & Newkirk 1990).…”
Section: Genetic Parameters and Genotype 3 Environment Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evans et al estimated the heritability of shell pigmentation using 18 full‐sib families by midparent–offspring regression, and the result proved to be reliable when compared with other results (Evans, Camara, & Langdon, ). Regarding variation in nutritional quality traits, glycogen, protein, lipid, and Zn contents display high variation among families, which is a basis for selective breeding (Li et al, ). In contrast, Se content did not differ between half‐sib families in this study, and conducting selective breeding for Se content is therefore likely impossible for the population analyzed here.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and phenotypical correlations between two traits include specific quantitative trait parameters that can be applied to predict the potentiality of traits to be improved together by selective breeding and be beneficial for determining proper breeding strategies (Falconer & Mackay, 1996). The most recent heritability studies on bivalves focused on traits related to growth (Frank-Lawale & Allen, 2008;Guinez, Toro, Krapivka, Alcapan, & Oyarzun, 2017;He, Guan, Yuan, & Zhang, 2008;Kong, Li, Yu, & Kong, 2015;Li, Wang, Liu, & Kong, 2011;Wang, Du, Lu, & Liu, 2010) and resistance to bacteria and viruses (i.e., to mortality) (Azema et al, 2017;Degremont, Lamy, Pepin, Travers, & Renault, 2015). The heritabilities of lipid percentage in Atlantic salmon and Coho salmon have also been estimated (Sodeland et al, 2013).…”
Section: Introductionmentioning
confidence: 99%